Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s00213-010-2103-5
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of sublingual salvinorin A, a naturally occurring kappa opioid, in humans: a placebo-controlled trial

Abstract: RationaleSalvinorin A (SA) is a highly selective kappa opioid receptor agonist and the putative psychoactive compound in Salvia divinorum (SD), an increasingly abused hallucinogenic plant.ObjectivesThe objectives of this study were to characterize the physiological and subjective effects of SA versus placebo and measure drug and metabolite levels.MethodsSublingual SA doses up to 4 mg were administered in dimethyl sulfoxide/polyethylene glycol 400 solution to eight SD-experienced subjects using a placebo-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…These first two reports provide almost no information on demographics of participants and little information on administration procedures and either behavioral or subjective effects of SA. Mendelson et al (2010) did not obtain any psychoactive effects in eight participants, presumably due to the unreliable nature of sublingual absorption of SA. Finally, Johnson et al (2010) completed a placebocontrolled dose-response study of inhaled SA in four participants, focusing on vital signs and objective measurements, of inebriation and briefly describing some subjective effects.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…These first two reports provide almost no information on demographics of participants and little information on administration procedures and either behavioral or subjective effects of SA. Mendelson et al (2010) did not obtain any psychoactive effects in eight participants, presumably due to the unreliable nature of sublingual absorption of SA. Finally, Johnson et al (2010) completed a placebocontrolled dose-response study of inhaled SA in four participants, focusing on vital signs and objective measurements, of inebriation and briefly describing some subjective effects.…”
Section: Introductionmentioning
confidence: 82%
“…divinorum contains a potent psychoactive which facilitates hallucinogenic states of consciousness under controlled conditions. Using safe and ethical research procedures (Johnson et al 2010;Mendelson et al 2010;Pichini et al 2005;Siebert 1994), the immediate and lasting effects of SA can be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Mendelson et al (2010) aimed to thoroughly investigate the effect of salvinorin A when administered sublingually. This placebo-controlled study examined the subjective effects (Subjective Drug Effects Questionnaire, Altered States of Consciousness Questionnaire, and Positive and Negative Affect Schedule) and physiological effects (heart rate, blood pressure, O 2 saturation, and body temperature) of an ascending dose (0 -4000 g sublingual) of salvinorin A solvated in 25% DMSO/75% polyethylene glycol.…”
Section: Effects Of Salvinorin a In Humansmentioning
confidence: 99%
“…Salvinorin A (122), a compound isolated from Salvia species, has Phytochem Rev been proved to have KOR affinity (Munro et al 2005). While a recent study showed sublingual dose up to 4 mg salvinorin A did not produce significant greater physiological or subjective effects than placebo (Mendelson et al 2011). The results suggested that the sublingual bioavailability of salvinorin A is low.…”
Section: Receptor Binding Affinitymentioning
confidence: 95%